Pb(II) and Oil Contamination Analysis of Belawan Sea, Medan City, North Sumatera - Lili Nur Indah Sari Tarigan; Nurul Qodri; Septi Lumongga Duma rangkuti; Moondra Zubir (Universitas Negeri Medan, 2019)
Belawan waters are very densely populated with shipping, industrial and settlement. These various activities have an impact in the form of sea pollution by liquid waste such as Pb (II) and oil. Based on the results of the analysis of the content of Pb (II) in the highest waters, which is equal to 26.9120 ppm, it exceeds the threshold. The oil content in the waters has exceeded the threshold of 0.05 gr / L. One way to reduce the levels of Pb (II) and oil is by using coconut husk biosorbent. This is evidenced by the results of the analysis that there was a decrease in Pb (II) metal content after adsorption using coconut coir biosorbent which was equal to 6.2430ppm with adsorption capability of 20,699 ppm. The oil content in the water after the water is adsorbed using coconut coir biosorbent shows the Not Applicable result because the seawater sample has been homogenized so that no significant changes occur. This shows that coconut coir biosorbent is effective to reduce the content of Pb and Oil in water in the waters of the sea.